PROSPECTS OF CHANGES IN THE VECTOR OF HIGHER EDUCATION DEVELOPMENT: RESULTS OF SCIENTIFIC RESEARCH - ZAHORIANSKA, Olena; ZAHORIANSKYI, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the paper the changes in the development vector of higher education under the influence of negative factors of the external environment are analyzed. It was established, on the example of the activities of the Kremenchuk Mykhailo Ostrohradskyi National University, that in recent years the number of students in regional higher education institutions has significantly decreased and there has been a problem of employment of scientific and pedagogical personnel who have scientific degrees, titles and publications, the leading place among which is publications in publications, that are indexed by the Scopus database. The problem is that recently there is no connection between such important participants of the educational process as the school-higher educational institutions-stakeholders. In today’s conditions of rapid development of information technologies, this connection should be very close, since there is strong competition not only among domestic higher education institutions, but also among foreign ones in the market of educational services. In such a competitive environment, not all higher education institutions have the opportunity to demonstrate their strengths. It is proposed to coordinate the activities of the participants of the educational process within the framework of the project "International educational and scientific park "school- higher educational institutions-stakeholders". The hierarchy of the structure of works related to the creation of the international educational and scientific park "school-university-university-stakeholders" has been defined and a grid model of the distribution of the complex of works into separate parts and their fixation by performers has been built. The implementation of this project provides an opportunity to create a multi-functional and multi-format scientific environment, which will contribute to the solution of tasks related to the formation of an educational environment through the functioning of scientific and educational hubs and online courses; introduction of mobile applications into the scientific and educational process as part of asynchronous learning; creation of electronic sociological laboratories, in particular with the use of crown funding tools; wide implementation of dual education as a tool for increasing the rating of regional universities.